2008
DOI: 10.1002/sce.20244
|View full text |Cite
|
Sign up to set email alerts
|

Raising cognitive load with linear multimedia to promote conceptual change

Abstract: Two disparate research programs have addressed the challenge of instructional multimedia design. One, based on cognitive load theory, has focused on ways of reducing unnecessary cognitive load during instruction to free up resources for learning. The other, based on constructivism, has centered on interactive multimedia, allowing students to build their own knowledge. Attempting to build on both bodies of literature, in this study, we investigated techniques that can raise the useful cognitive load engendered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…Inquiry-based learning with simulations is a promising area for science-based instruction to foster learners' mental interaction with the physical and social world in order to develop scientific understanding, explanation, and communication among science ideas. Researchers have found that SimIn learning works as a remedial process by producing change in the alternative conceptions held by learners (Bell and Trundle 2008;Jimoyiannis and Komis 2001;Muller et al 2008;Srisawasdi et al 2013;Srisawasdi and Kroothkeaw 2014;Srisawasdi and Sornkhatha 2014;Windschitl and Andre 1998;Zacharia and Anderson 2003), improving the performance of gaining intuitive domain-specific knowledge, and promoting more qualitative knowledge than formalized knowledge (de Jong et al 1999;Veemans et al 2006;Suits and Srisawasdi 2013), achieving a more theoretical focus and coherent understanding of the concepts (Winberg and Berg 2007), and promoting positive perception of science learning (Buyai and Srisawasdi 2014;Pinatuwong and Srisawasdi 2014).…”
Section: Simulation-based Inquiry Learning In Sciencementioning
confidence: 99%
“…Inquiry-based learning with simulations is a promising area for science-based instruction to foster learners' mental interaction with the physical and social world in order to develop scientific understanding, explanation, and communication among science ideas. Researchers have found that SimIn learning works as a remedial process by producing change in the alternative conceptions held by learners (Bell and Trundle 2008;Jimoyiannis and Komis 2001;Muller et al 2008;Srisawasdi et al 2013;Srisawasdi and Kroothkeaw 2014;Srisawasdi and Sornkhatha 2014;Windschitl and Andre 1998;Zacharia and Anderson 2003), improving the performance of gaining intuitive domain-specific knowledge, and promoting more qualitative knowledge than formalized knowledge (de Jong et al 1999;Veemans et al 2006;Suits and Srisawasdi 2013), achieving a more theoretical focus and coherent understanding of the concepts (Winberg and Berg 2007), and promoting positive perception of science learning (Buyai and Srisawasdi 2014;Pinatuwong and Srisawasdi 2014).…”
Section: Simulation-based Inquiry Learning In Sciencementioning
confidence: 99%
“…Cox et al (1999) while investigating learning using dialogues on computers, have shown that students who do not actively participate in discussions also benefit through 'vicarious' learning (observing other people discussing ideas). Muller et al (2008) demonstrated that students watching a student and a tutor discussing misconceptions in a short linear video showed larger learning gains than those who watched a video containing just the correct content. The student and tutor dialogue was carefully based on common misconceptions from literature.…”
Section: On the Format Of Classroom Discussionmentioning
confidence: 96%
“…One can argue that such detail can introduce misconceptions and that is likely to be what Sam is trying to resolve. However, the resulting discussion shown below does not evolve into a misconceptions-based dialogue such as those scripted by Muller et al (2008).…”
Section: Whole Class Treatmentmentioning
confidence: 92%
“…However, it was obviously inconvenient to conduct quantitative analysis (Zhang and Chen, 2000;Ifenthaler et al, 2001). So the researchers developed some new methods, such as flow-map method (Anderson and Demetrius, 1993) , the technique of "establishment by the subject" (Liu, 1994;Enger, 1996;Ruiz-Primo & Shavelson, 1997;Ruiz-Primo et al, 2001;Lavigne, 2005;Shavelson et al, 2005;Muller et al, 2008;Lindstrom & Sharma, 2011), the method of "Pathfinder Associative Networks" (Casas et al, 2011;Geeslin & Shavelson, 1975;Jonssen et al, 1993;Fenker, 1975;Preece, 1976;Wainer & Kaye, 1974), and the method with HIMATT (Ifenthaler, 2011). After verifying by practice, it could be found these new methods were feasible, they promoted the quantitative research to cognitive structure and made the understanding of MCS to be more distinct and profound.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%